Absorção de N, P, K por plantas de soja em solo sob variação de compactação - Matté, Marina Fabris (2019)
Concern over soil compaction is an old problem, which is increasingly gaining ground among farmers. This process is mainly due to the high traffic of machines exerting unavoidable external pressures on the ground, making it compact and difficult to handle. With this, there is a low infiltration of the water, causing erosions, taking with it the minerals necessary for the plants to develop. The nitrogen, phosphorus and potassium elements are some of these, which play important role in plant metabolism. Thus, the objective of this work was to present analyzes of the amount of N, P and K that a soybean plant absorbs in its vegetative period up to the R1 phase. The seeds were planted in pots, with five levels of soil compacts, being these densities of 1,1; 1,2; 1,3; 1.4 and 1.5 Mg ha-1 in a ring 10 centimeters high with 20 centimeters in diameter. In conclusion, for N, the densities of 1.4 Mg ha -1 and 1.5 were statistically significant (P> 0.05), showing that the amount of nutrient absorbed by the plants was better in a higher degree of compaction, for (P> 0.05), the best result was verified in relation to the amount absorbed by the plants . This work was carried out with the support of the Coordination of Improvement of Higher Education Personnel - Brazil (CAPES) - Financing Code 001.